Analysis of the Implementation of Good Governance Principles in the DKI Jakarta Province Bakesbangpol Strategic Program: Review of the 2022 Work Plan and Realization - Putri, Almirah Ghaisani; Desita, Maria Mariska; Nurcahyani, Nabila Putri; Aji, Muhammad Prakoso (Journal of Governance and Administrative Reform, 2025)
Abstract This study aims to analyze the implementation of good governance principles in the strategic programs of the National Unity and Politics Agency (Bakesbangpol) of DKI Jakarta Province by assessing the alignment between planning documents (Renstra and Renja) and program outcomes in 2022. The principles of good governance, including participation, accountability, transparency, rule of law, consensus, responsiveness, equity, inclusiveness, as well as effectiveness and efficiency, serve as the analytical framework. Employing a library research methodology, this study examines official documents, performance reports, and relevant academic literature. The findings suggest that Bakesbangpol DKI Jakarta has successfully implemented the eight principles of Good Governance in its strategic programs, as evidenced by exceeding performance targets, public engagement, and information transparency. However, further evaluation is required to assess the programs' transformative and long-term impact on society. Keywords: good governance; bakesbangpol; public governance Abstrak Penelitian ini bertujuan untuk menganalisis penerapan prinsip-prinsip good governance dalam program strategis Badan Kesatuan Bangsa dan Politik Provinsi DKI Jakarta dengan menilai keselarasan antara dokumen perencanaan  dan hasil program pada tahun 2022. Prinsip-prinsip good governance, termasuk partisipasi, akuntabilitas, transparansi, supremasi hukum, konsensus, responsivitas, kesetaraan, inklusivitas, serta efektivitas dan efisiensi, digunakan sebagai kerangka analisis. Menggunakan metode penelitian pustaka, studi ini menganalisis dokumen resmi, laporan kinerja, dan literatur akademik terkait. Hasil penelitian menunjukkan bahwa Bakesbangpol DKI Jakarta telah berhasil menerapkan kedelapan prinsip good governance dalam program strategisnya, meskipun evaluasi lebih lanjut diperlukan untuk menilai dampak transformasional dan jangka panjang program-program tersebut terhadap masyarakat. Kata kunci: good governance; bakesbangpol; tata kelola pemerintahan.